Tadpoles of the High-Andean Hyloxalus subpunctatus (Anura: Dendrobatidae) with description of larval variation and species distinction by larval morphology - Anganoy-Criollo, Marvin (Papéis Avulsos de Zoologia, 2013)
This study redescribes the tadpoles of Hyloxalus subpunctatus (Anura: Dendrobatidae) based on larvae from the type locality and over most of its geographic range, including all stages of ontogenetic development. I describe tadpoles in the three developmental phases: (1) back-riding tadpoles, (2) free-swimming tadpoles, (3) froglets or individuals in metamorphosis. The larval morphology showed at least two types of variation: ontogenetic variation and variation within each developmental phase. In back-riding tadpoles, the variation in labial tooth rows suggests a pattern of the labial tooth row formation. In free-swimming tadpoles there is variation in the disposition of marginal papillae, i.e., in the number of rows on the margin of the lips, but this variation has no effect on the general aspect of the tadpoles. Moreover, I compared the tadpoles of H. subpunctatus with tadpoles of potential sympatric species and populations previously identified as H. subpunctatus. Interspecific differences and larval characters were found that were useful in delimiting those species.